Citizenship competencies: a conceptual reconstruction within the framework of the Costa Rican Civic Education - Arce Ramírez, Henry (2019)
This essay presents a conceptualization of the civic competencies inside the Costa Rican educational context by means of an analysis of theoretical and practical positions from different authors. This evaluation of the approach performed in the dimension of the civic competencies program of the 2009 study of Civic Education, is to generate spaces to reflect on the proposed plan of the Ministry of Public Education in relationship to the competencies for the active participation and the democratic coexistence that will strengthen the quality of life of the students in society, thus making a positive impact in their lives. The main conclusions of this work emphasize the coherence of the proposal of civic skills/competencies within the analyzed theoretical and methodological modality, the importance of pedagogic mediation, the responsibility of teachers in the integral formation of the students, and, the need to extend this type of civic teaching and learning in all subjects of the curriculum.